Stimulation of frontal cortex and delayed alternation performance in the monkey. - Weiskrantz, L; Mihailovic, L; Gross, C (1960)
Unilateral or bilateral stimulation of the region surrounding the sulcus principalis of the cortex of the monkey interferes with delayed alternation performance. It is without effect on auditory discrimination performance. Bilateral stimulation is more disrupting than unilateral stimulation. The impairment is limited in time to the period of stimulation and is fully reversible.